promotion image of download ymail app
Promoted

How does LHS equal RHS?

http://www.imagehosting.nu/images/equality.png

Can someone tell me how does the LHS side of the equation equal the right hand side?

Thanks.

2 Answers

Relevance
  • Anonymous
    8 years ago
    Favorite Answer

    Let...[1 / 2*square root of X] = K

    LHS = K / (X-2)....multiply top and bottom by -1 ...= -K / -(X -2) = -K / (2 -X ) = RHS

    • Commenter avatarLogin to reply the answers
  • 8 years ago

    LHS = RHS because (x-2) = - (2-x)

    • Commenter avatarLogin to reply the answers
Still have questions? Get your answers by asking now.